2003
DOI: 10.1189/jlb.0902443
|View full text |Cite
|
Sign up to set email alerts
|

Ly49E expression points toward overlapping, but distinct, natural killer (NK) cell differentiation kinetics and potential of fetal versus adult lymphoid progenitors

Abstract: Using a new antibody, we found previously that contrary to adult natural killer (NK) cells, fetal NK cells have a unique phenotype, as they exclusively express Ly49E. This can be explained by an intrinsic different NK differentiation potential of fetal versus adult lymphoid progenitors, by immaturity of fetal NK cells or by instability of Ly49E expression. Here, we show that adult progenitor cells were still capable of differentiating into Ly49E-expressing NK cells but at a much lower frequency. Surprisingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The deficiency in expression of the other Ly49 family members in vivo could be a consequence of the relatively early time point examined in this experiment, as it is known that some family members, including Ly49A and D, are expressed at relatively late time points after BM reconstitution [25]. An inability to express appropriate levels of the Ly49 family members, with the exception of Ly49E, has also been observed in fetal-as well as embryonic stem cell-derived NK cells [25][26][27] and, very recently, in thymus-derived NK cells (Vosshenrich et al, in press), suggesting that the Pax5 -/-pro-B cell-derived NK cells differentiate along a similar pathway in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…The deficiency in expression of the other Ly49 family members in vivo could be a consequence of the relatively early time point examined in this experiment, as it is known that some family members, including Ly49A and D, are expressed at relatively late time points after BM reconstitution [25]. An inability to express appropriate levels of the Ly49 family members, with the exception of Ly49E, has also been observed in fetal-as well as embryonic stem cell-derived NK cells [25][26][27] and, very recently, in thymus-derived NK cells (Vosshenrich et al, in press), suggesting that the Pax5 -/-pro-B cell-derived NK cells differentiate along a similar pathway in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that Ly49E is expressed abundantly, and in the absence of other Ly49 family members, by NK cells in fetal and neonatal mice (15,16), and also by V␥3-bearing subpopulations of ␥␦ T cells in vivo (18). Ly49E is acquired in a stochastic manner during the development of NK cells from immature progenitors, both in vitro (17) and in vivo (50), but is lost at some later point in development resulting in its being expressed on only a very small proportion of adult splenic NK cells. The detection of Ly49E in these previous studies relied on the use of the 4D12 mAb, which also reacts with Ly49C and perhaps with other members of the Ly49 family (16).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16]22,29,30 However, little is known about actual molecular signals that induce the expression and control the acquisition of Ly49 and CD94/NKG2 receptors. Recent studies on mice deficient for the transcription factors T-cell factor-1 (TCF-1), PU.1, and GATA3 indicated a role for these transcription factors in the modulation of expression of some Ly49 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of the different Ly49 members occurs in an orderly and time-dependent fashion, where Ly49A is the last receptor to be expressed, and where CD94/NKG2 expression is high at early time points and decreases thereafter. 22 Therefore, small differences in the rate of NK cell differentiation between both strains could explain the minor differences in Ly49A receptor and CD94/ NKG2 receptor repertoire. …”
mentioning
confidence: 99%